Climate and Human Impacts on Hydrological Processes and Flood Risk in Southern Louisiana. Issue 2 (17th February 2023) - Getirana, Augusto; Kumar, Sujay; Konapala, Goutam; Nie, Wanshu; Locke, Kim; Loomis, Bryant; Birkett, Charon; Ricko, Martina; Simard, Marc
Abstract: Satellite observations of coastal Louisiana indicate an overall land loss over recent decades, which could be attributed to climate and human‐induced factors, including sea level rise (SLR). Climate‐induced hydrological change (CHC) has impacted the way flood control structures are used, altering the spatiotemporal water distribution. Based on "what‐if" scenarios, we determine relative impacts of SLR and CHC on increased flood risk over southern Louisiana and examine the role of water management, via flood control structures, in mitigating flood risk over the region. Our findings show that CHC has increased flood risk over the past 28 years. The number of affected people increases as extreme hydrological events become more exceptional. Water management reduces flood risk to urban areas and croplands, especially during exceptional hydrological events. For example, currently (i.e., 2016–2020 period), CHC‐induced flooding puts an additional 73 km 2 of cropland under flood risk at least half of the time (median flood event) and 65 km 2 once a year (annual flood event), when compared to a past period (1993–1997). A 10‐ to 20‐fold increase relative to SLR‐induced flooding. CHC also increases population vulnerability in southern Louisiana to flooding; additional 9, 900 residents currently live under flood risk at least half of the time, and that number increases to 27, 400 for annual flood events. Residents vulnerable to SLR‐induced flooding is lower (6, 000 and 3, 300 residents, respectively). Conclusions are that CHC is a major factor that should be accounted for flood resilience and that water management interventions can mitigate risks to human life and activities. Plain Language Summary: Current scientific literature defines sea level rise as a major factor in increasing global coastal flood risk in recent and future decades, showing that coastal flood risk, particularly over southern Louisiana, is exacerbated by natural and human‐induced subsidence. However, the impacts of climate‐induced hydrological change (CHC) on flooding and synergy with sea level rise (SLR) are often overlooked. Here, we quantify how CHC affect southern Louisiana's water dynamics and its synergy with SLR and water management that results land loss and increase in terrestrial water storage over the decades. We look to answer how much of observed changes are due to CHC and SLR, what are their individual contributions to increasing flood risk, and how local water management contributes to flood resilience. Key Points: Impacts of climate‐induced hydrological change (CHC), water management and sea level rise (SLR) on Louisiana flooding are quantified CHC increased flood risk over the past 28 years; flood control structures are vital in protecting Louisiana's major cities and croplands SLR‐induced increase in median net flooded area exceeds CHC's; but annual events are more severely impacted by CHC